(3QSGdI dbW GdLhGgQ aj JMOjO GdNWhW hGdOhGFQs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI GdfbWg TF ef PhGJ GdChVGY dGLRA dg hGdNW eGdg Whd abW s
(3BNQgG (B:s
(3heQGOi Hg GdCab GdMbjbi dG GdeQi hajg HMK PcQJg ai QSGdJi GdeSeGg HGdeWdH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93 - (3U(B100s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B167 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B167) s
Keywords: (3Gdadcs